Combining Resting-state fMRI and DTI Analysis for Early-onset Schizophrenia - Ming Ke (International Journal of Computational Intelligence Systems, 2009)
We combined measures of resting-state functional magnetic resonance imaging and diffusion tensor imaging (DTI) to investigate alterations of function-structure relationships in patients with early-onset schizophrenia. DTI analysis revealed reduced fractional anisotropy in right frontal white matter. Corresponding gray matter regions showed reduced functional connectivity with other regions in the brain in patients with early-onset schizophrenia, compared with healthy controls. Our results demonstrated abnormal function-structure relationships in early-onset schizophrenia, and supported the view that white matter lesions might disrupt the neural circuits between frontal regions and other brain regions, and affect the functional connectivity in the frontal cortex.